Improving the high-temperature oxidation resistance of ASME-SA213-T11 boiler tube steel by plasma spraying with CNT-reinforced alumina coatings. Issue 2 (5th March 2018) - Goyal, Rakesh; Sidhu, Buta Singh; Chawla, Vikas
Abstract : Purpose: This paper aims to discuss that a conventional Al2 O3, 1.5 Wt.% carbon nanotubes (CNTs)-Al2 O3, 2 Wt.% CNTs-Al2 O3 and 4 Wt.% CNTs-Al2 O3 composite coatings were deposited with the help of Plasma spray process. Design/methodology/approach: To better understand the effect of CNT reinforcement on oxidation resistance, high-temperature oxidation behaviour of conventional Al2 O3, 1.5 Wt.% CNTs-Al2 O3, 2 Wt.% CNTs-Al2 O3 and 4 Wt.% CNTs-Al2 O3 composite coatings at 900°C was compared with the performance of the uncoated ASME-SA213-T11 boiler tube steel substrate. Findings: The results showed that the CNT-reinforced alumina coatings exhibited better oxidation resistance and thermal stability than uncoated ASME-SA213-T11 boiler tube steel. The coated steel substrates had a lower mass gain rate than the substrate after different oxidation times. Originality/value: Limited literature is available where the CNT have been reinforced into the composite alloy powders and has been thermally spray-deposited for various surface engineering applications. This research showed that with the increase in the percentage of CNTs into the alloy powder mixture, there is a significant reduction in weight gain and hence higher resistance to oxidation.